2006
DOI: 10.1159/000094004
|View full text |Cite
|
Sign up to set email alerts
|

Central Thyrotropin-Releasing Hormone Infusion Opposes Cardiovascular and Metabolic Suppression during Caloric Restriction

Abstract: Inhibition of hypothalamic thyrotropin-releasing hormone (TRH) neuronal activity is a well-established adaptation to caloric restriction (CR) that suppresses pituitary secretion of thyroid-stimulating hormone, but may also participate in modulation of autonomic function. Thus, we hypothesized that decreased hypothalamic TRH activity contributes to CR-induced bradycardia and decreased metabolic rate. To test this hypothesis, male Sprague-Dawley rats were instrumented with telemetry devices for measurement of he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 88 publications
(55 reference statements)
1
6
0
Order By: Relevance
“…Furthermore, we (8,12) have consistently found that diencephalic TRH manipulation does not necessarily change thyroid status. This have been confirmed by other groups in different settings (23).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Furthermore, we (8,12) have consistently found that diencephalic TRH manipulation does not necessarily change thyroid status. This have been confirmed by other groups in different settings (23).…”
Section: Discussionsupporting
confidence: 84%
“…Accordingly, in our hands, TRH AS treatment was effective and selective in decreasing the elevated concentrations of NMN and MN of obese animals, which added additional evidence to the existence of a TRH-dependent elevation of ABP mediated by sympathetic overflow. Interestingly, prepro-TRH siRNA treatment induced a significant increase in body weight, indicating that diencephalic TRH serves as a negative modulator of body weight gain, probably by acting on energy balance (21,23,24).…”
Section: Discussionmentioning
confidence: 99%
“…Thyrotropin-releasing hormone (TRH), known to have central effects on the control of the autonomic nervous system (23)(24)(25), excited 48% ( Figure 3D) and inhibited 19% of the neurons. Some of these inhibitions were associated with an increase in inhibitory postsynaptic potentials (Supplemental Figure 2, F and G), suggesting that the AHA pv + neurons are part of a TRH excited inhibitory network.…”
Section: Figurementioning
confidence: 99%
“…Basing our conclusions on the knowledge that cardiovascular effects of dTRH are mediated by the sympathetic system [24,25], we propose that the leptin-induced sympathetic tone may be mediated by a dTRH increase. In fact, these results are in agreement with those that we found in an obese rat model induced by a high-fat diet in which the elevation of body weight is accompanied by hyperleptinemia, dTRH elevation, and hypertension with elevation of the sympathetic tone.…”
Section: Discussionmentioning
confidence: 70%